Sex disparities in alcohol-associated liver disease and subtype differences in alcohol-attributable cancers in the United States - Pojsakorn Danpanichkul; Yanfang Pang; Tanuj Mahendru; Primrose Tothanarungroj; Luis Antonio Díaz; Juan Pablo Arab; Pimtawan Jatupornpakdee; Mark D. Muthiah; Kwanjit Duangsonk; Won-Mook Choi; Daniel Q. Huang; Donghee Kim; et al. (Clinical and Molecular Hepatology)
Background/Aims Harmful alcohol use is a substantial contributor to liver diseases, liver cancer, and extrahepatic neoplasms. Patterns of alcohol consumption have shifted over recent decades. This study evaluates trends in alcohol-associated liver disease (ALD) and alcohol-attributable cancers in the United States (US) from 2000 to 2021. Methods Using the methodological framework of the Global Burden of Disease Study 2021, we analyzed trends in incidence, prevalence, and mortality from ALD and alcohol-attributable cancers in the US. Results In 2021, there were 28,340 new cases of ALD, 227,730 prevalent cases, and 21,860 deaths attributed to ALD in the US. From 2000 to 2021, ALD incidence, prevalence, and mortality increased by 43%, 36%, and 79%, respectively. The age-standardized incidence and death rate of ALD rose disproportionately among females compared to males. For alcohol-attributable cancers, primary liver cancer, colorectal cancer, and esophageal cancer accounted for the largest share of deaths in 2021. Age-standardized death rates increased significantly for primary liver cancer (annual percent change [APC] 2.21%, 95% confidence interval [CI] 1.70–2.73%) and other pharyngeal cancer (APC 1.35%, 95% CI 1.08–1.62%). Conclusions The burden of ALD is substantial and continues to rise in the US, with a particularly notable increase among females. Mortality from alcohol-attributable cancers is also increasing, mainly driven by primary liver cancer and pharyngeal cancer. However, system-wise, gastrointestinal cancer had the highest death attributable to alcohol. These findings highlight the urgent need for public health strategies to tackle ALD, primary liver cancer, and alcoholattributable extrahepatic malignancies.